Aktivitas Antioksidan dari Air Buah Beruwas Laut (Scaevola taccada): Antioxidant Activities of Beach Naupaka's Water (Scaevola taccada) - Azwin Apriandi; Zubaidah Anjar Rezeki; Kiki Fatmawati; Sri Novalina Amrizal; R. Marwita Sari Putri (Jurnal Pengolahan Hasil Perikanan Indonesia, 2021)
Scaevola taccada (Beach Naupaka) is common plant found on Indonesia coast.This study was aimed to determine antioxidant activity and levels of vitamin C contained in the juice of old, young, and mixed beach naupaka's fruit. Antioxidant activity was tested using DPPH method and vitamin C levels using the iodimetric titration m. The results obtained showed that the antioxidant activity of beach naupaka were 113.47 ppm for old fruit, 130.71 ppm for young fruit, 164.58 ppm for mixed fruit. Vitamin C levels of old, young, and mixed fruit water were 7.04 mg, 36.96 mg, and 30.8 mg respectively.